. Influence of the use of special exercises on the psychophysiological indicators of young boxers aged 15-16 - Yuri Shestak; Viacheslav Mulyk; Daria Okun (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the effectiveness of the use of special exercises using boxing equipment during a one-year macrocycle in young boxers 15-16 years old. Material and methods: the research was carried out with the involvement of young boxers 15-16 years old, who made up the control (12 athletes) and experimental (12 athletes) groups, who carried out a year-long training process according to the CYSS program, but in the experimental group at the end of each training exercise using boxing equipment (exercises with a bag and a pear, with a wall pillow; pneumatic bag; exercises with a ball on elastic bands; exercises with a small hanging ball). The initial and final measurements of psychophysiological parameters were carried out after training with a high load, which was used in boxers of both groups. Result: the results obtained make it possible to expand the methodology of using special exercises for the development of speed-strength qualities in accordance with the specificity of the sport. The expediency of using exercises of a special speed-strength orientation in young boxers of 15-16 years old at the end of a training session, against the background of fatigue, is determined. Conclusions: the improvement of the results of psychophysiological indicators, which are the components of the motor activity of boxers (the time of a simple reaction to sound and light; Romberg's test, indicators of the Schulte test, concentration and switching of attention according to the Bourdon test) was confirmed.